2005
DOI: 10.1007/s00394-005-0573-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved fatty acid and leukotriene pattern with a novel lipid emulsion in surgical patients

Abstract: Treatment with the new emulsion SMOFlipid is well tolerated and modulates FA and leukotriene pattern suggesting favourable anti-inflammatory effects and further clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
4
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 37 publications
8
114
4
6
Order By: Relevance
“…05) than soyabean oil (62) . Taken together, these studies indicate that inclusion of fish oil in parenteral nutrition regimens for gastrointestinal surgical patients modulates the generation of inflammatory eicosanoids (61,62,66,67) and cytokines (4,66,68) and may help to counter the surgery-induced decline in antigen presenting cell activity (68) and T lymphocyte cytokine production (69) . Importantly, these studies do not reveal any deleterious effects of fish oil infusion in these patients.…”
Section: 5 D)mentioning
confidence: 98%
See 1 more Smart Citation
“…05) than soyabean oil (62) . Taken together, these studies indicate that inclusion of fish oil in parenteral nutrition regimens for gastrointestinal surgical patients modulates the generation of inflammatory eicosanoids (61,62,66,67) and cytokines (4,66,68) and may help to counter the surgery-induced decline in antigen presenting cell activity (68) and T lymphocyte cytokine production (69) . Importantly, these studies do not reveal any deleterious effects of fish oil infusion in these patients.…”
Section: 5 D)mentioning
confidence: 98%
“…Intravenous infusion of lipid emulsions containing fish oil into patients following gastrointestinal surgery altered the fatty acid composition of plasma (61)(62)(63)(64) , platelet (65) and erythrocyte (64) phospholipids: typically EPA content was increased. Intravenous infusion of a lipid emulsion containing fish oil into patients for 5 d following gastrointestinal surgery also altered the fatty acid composition of leucocytes: EPA content was increased 2 .…”
Section: Studies Of Parenteral Fish Oil In Surgical Patientsmentioning
confidence: 99%
“…Parenteral treatment with an emulsion with reduced content of n-6 fatty acids, increased share of MUFA and n-3 FA and supplemental vitamin E is well tolerated and modulates FA and leukotriene pattern, suggesting favourable anti-inflammatory effects and further clinical benefits [7]. Fig.…”
Section: Fish Oil and Cancer Cachexiamentioning
confidence: 98%
“…05) than soyabean oil (42) . Taken together, these studies indicate that inclusion of fish oil in parenteral nutrition regimens for patients who have undergone gastrointestinal surgery modulates generation of inflammatory eicosanoids (43)(44)(45)(46) and cytokines (44,47) and may help to counter the surgery-induced decline in antigen-presenting-cell activity (47) and production of T-lymphocyte cytokines (48) . Importantly, these studies do not reveal any deleterious effects of fish oil infusion in these patients.…”
Section: Studies Of Fish Oil In Patients Following Surgerymentioning
confidence: 99%
“…This outcome would be expected to impact on the profile of eicosanoids produced from arachidonic acid and EPA. Indeed, several studies have demonstrated that intravenous infusion of lipid emulsions containing fish oil into patients who had undergone major gastrointestinal surgery results in lower production of arachidonic acid-derived eicosanoids and higher production of EPA-derived eicosanoids by blood leucocytes stimulated ex vivo (43)(44)(45)(46) . Plasma TNFa concentrations are lower at day 6 post surgery while plasma IL-6 New lipid emulsions in parenteral nutrition (44) .…”
Section: Studies Of Fish Oil In Patients Following Surgerymentioning
confidence: 99%